Lenvatinib resistance mechanism and potential ways to conquer - Bo, Wentao; Chen, Yan (Frontiers in Pharmacology, 2023)
Lenvatinib (LVN) has been approved to treat advanced renal cell carcinoma, differentiated thyroid carcinoma, and hepatocellular carcinoma (HCC). Other cancer types have also been tested in preclinical and clinical settings without approval by the FDA. The extensive use of LVN in clinical practice is sufficient to demonstrate its important therapeutic role. Although drug resistance has not arisen mainly in clinical settings, studies have increasingly focused on LVN resistance. To keep up with the latest progress in the resistance caused by LVN, we summarized the latest studies from identified published reports. In this review, we found the newest report on resistance caused by lenvatinib, which contained a hotspot mechanism such as epithelial-mesenchymal transition, ferroptosis, and RNA modification. Nanotechnology, CRISPR technology, and traditional combined strategies embraced the potential ways to overcome LVN resistance. The latest literature review of LVN-related resistance would provide some methods for further study of LVN. We call for more attention to the pharmacological parameters of LVN in the clinical setting, which is rare and would supply critical elements for the drug's use in humans. Additionally, it would help to find resistance targets or ideas for further study.